Dinding Transparan: Tantangan Keterbukaan Diri (Self-Disclosure) dan Kerentanan dalam Persahabatan Virtual - Fatimah Sukandar (Jurnal Psikologi, 2026)
The "Transparent Wall" paradox, a complicated socio-psychological phenomenon where the line between intense emotional closeness and serious security dangers becomes progressively blurred, has emerged in the modern digital landscape as a result of virtual communication. With an emphasis on how personal vulnerability is heightened in the digital realm, this article offers a critical analysis of the complex issues surrounding self-disclosure in relationships mediated by technology. This study finds that the Online Disinhibition Effect is the main cause of increased closeness by examining the mechanics of online interactions. People are frequently encouraged by this tendency to circumvent conventional social filters, which results in "oversharing" habits that put them at serious danger of identity theft, emotional manipulation, and privacy breaches. The study also examines the false sense of security that the digital screen offers; although users may feel physically isolated and safe, their digital footprints are always present and reachable, resulting in a "transparent" condition of exposure. The results of a qualitative synthesis of communication theories, including Communication Privacy Management, show that the absence of non-verbal clues in virtual friendships frequently leads to a "false sense of security." As a result, this paper suggests that it is crucial to create an advanced private navigation system that is based on emotional intelligence and digital literacy. For people to maintain a healthy balance between the essential need for self-defense and the basic human need for connection, such a system is essential. This balance is essential to mitigate the long-term psychological and security-related repercussions of living in an interconnected, yet vulnerable, virtual world.